2017
DOI: 10.3389/fpsyt.2017.00217
|View full text |Cite
|
Sign up to set email alerts
|

Poor Illness Perceptions Are a Risk Factor for Depressive and Anxious Symptomatology in Fibromyalgia Syndrome: A Longitudinal Cohort Study

Abstract: BackgroundPatients with widespread pain, such as in fibromyalgia, are vulnerable for depression and anxiety, which composes a relevant public health problem. Identifying risk factors for the onset of depression and anxiety is therefore warranted. Objective of this study was to determine whether severe pain, maladaptive coping, and poor illness perceptions are associated with depressive and anxious symptomatology in fibromyalgia.MethodConsecutive patients referred to an outpatient clinic completed sets of physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
1
13
1
Order By: Relevance
“…This result is aligned with what we observe in a clinical setting, where the severity of psychological symptoms is a factor associated with the severity of the disease, and it has been demonstrated that it can be a predictive factor of treatment response. [51][52][53] The multivariate model showed that these symptoms are positively correlated to dysfunction in the DPMS. Thus, this result confirms our hypothesis that the severity of fibromyalgia symptoms, related to psychological characteristics, may indicate the failure of DPMS.…”
Section: Discussionmentioning
confidence: 99%
“…This result is aligned with what we observe in a clinical setting, where the severity of psychological symptoms is a factor associated with the severity of the disease, and it has been demonstrated that it can be a predictive factor of treatment response. [51][52][53] The multivariate model showed that these symptoms are positively correlated to dysfunction in the DPMS. Thus, this result confirms our hypothesis that the severity of fibromyalgia symptoms, related to psychological characteristics, may indicate the failure of DPMS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anxious patients exhibited worse perceptions about consequences, sense of control, and symptoms. 48 A recent longitudinal study 49 has described the role of some dimensions of illness perception (emotional representations, control over the treatment, and perceived consequences of the disease), as well as level of anxiety and depressive symptoms which may predict a possible/probable anxiety disorder at 18-month follow-up. Lastly, an additional study in patients with chronic widespread pain has suggested that higher impact of the disease on emotional and physical well-being is linked to the presence of increased levels of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the label someone gives to his/her illness (Identity), the control perceived over his/her treatment, how much the illness is understood, and the emotional impact of the disease seem to be predictors of depressive symptoms. 51 Further studies have shown that other dimensions of illness perception can predict the onset of depressive symptoms: 49 duration and negative consequences of the illness. 52 Moreover, in another study on chronic heart failure, results indicated that patients who perceive their illness to be burdensome and threatening and experience low personal control over it contribute to increased depressive symptoms and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that IPs are predictive for and associated with psychological factors, such as depression and anxiety, in patients with fibromyalgia [ 14 ], chronic back pain [ 15 ] systemic lupus erythematosus [ 16 ] and informal carers of patients with depression [ 17 ]. Therefore, overlap may exist between the domains included in the 4DSQ and in the Brief IPQ.…”
Section: Introductionmentioning
confidence: 99%